The Role of History Teachers in Increasing Students' Learning Motivation at SMA Negeri 5 Palu - Rezki Zakinah (Journal of Education and Teaching Learning, 2026)
This study aims to determine the role of history teachers in enhancing students' learning motivation at SMA Negeri 5 Palu. The method employed in this research is descriptive qualitative. Data were collected through observation, interviews, and documentation. The findings indicate that the role of history teachers is highly crucial in increasing students' learning motivation through the use of engaging instructional methods, the continuous provision of motivation, the utilization of varied learning media, and the creation of an active and enjoyable learning atmosphere. Teachers also function as facilitators, motivators, and mentors who are capable of connecting historical material to students' daily lives, thereby making the learning process more meaningful. The conclusion of this study demonstrates that the role of history teachers in enhancing student motivation is executed through planned and effective strategies, namely the implementation of varied teaching methods, the use of appropriate media, the provision of individual attention and encouragement, and the creation of a conducive learning environment. These efforts successfully enhance students' interest, enthusiasm, and participation in history learning, allowing the instructional objectives to be optimally achieved.